The Arbitrage Pricing Model and Returns on Assets Under Uncertain Inflation: Discussion - Bodie, Zvi (Journal of Finance, 1983)
Zvi Bodie, The Arbitrage Pricing Model and Returns on Assets Under Uncertain Inflation: Discussion, The Journal of Finance, Vol. 38, No. 2, Papers and Proceedings Forty-First Annual Meeting American Finance Association New York, N.Y. December 28-30, 1982 (May, 1983), pp. 563-564